2003
DOI: 10.1889/1.1832281
|View full text |Cite
|
Sign up to set email alerts
|

P‐38: Driving Scheme for Improving Color Performance of LCD's: Accurate Color Capture

Abstract: This paper describes a novel driving scheme, ACC Accurate Color Capture, for improving color accuracy of LCD's. ACC changes RGB gamma curves separately to reduce the color shift with respect to the gray level. ACC dramatically reduced correlated color temperature shift from 3300K to 75K through 255‐64 gray range with 2.4 gray gamma value. As experimental results, ACC is little affected by gamma value variation of 2.0–2.8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Figure 1 shows the operation diagram of the analog T-T type pixel. The input gray level (R, G, B) would enter one RGB LUT, which minimizes the on-axis white-color shift vs. gray level [10]. Then, the output gray level (R', G', B') of the RGB LUT would be the common input signal for the two individual sets of R-string networks (for main-regions and subregions, respectively), which determines output voltages, Vmain and Vsub, as a function of the gray level.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the operation diagram of the analog T-T type pixel. The input gray level (R, G, B) would enter one RGB LUT, which minimizes the on-axis white-color shift vs. gray level [10]. Then, the output gray level (R', G', B') of the RGB LUT would be the common input signal for the two individual sets of R-string networks (for main-regions and subregions, respectively), which determines output voltages, Vmain and Vsub, as a function of the gray level.…”
Section: Resultsmentioning
confidence: 99%
“…This kind of problem can appear especially on multi-domain structures designed for wide viewing angle performance, and the yellowing artifact is investigated by means of experiments that follow. Figure 2 shows the result of applying ACC (Accurate Color Capture) [5] correction technology on a 2G-1D multi-domain structure. With ACC, the input red, green and blue gray data is adjusted to correct for the wavelength-dependent dispersion of liquid crystals to achieve white balance over all gray levels onaxis.…”
Section: Experiments 21 Oblique Viewing Angle Image Quality and Color mentioning
confidence: 99%
“…In addition, with the introduction of DID, digital gamma correction [6] needs to be re-examined for its effectiveness, since the LC response is now impulsive, and the color performance may be different. Overdrive, DID, and DGC hardware were developed, and their optical performances that are core to a high quality TFT-LCD, are compared.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to slow response time of liquid crystal displays, we have found that overdrive is necessary for good motion picture performance of DID, and in extreme cases, DID without overdrive has worse motion picture performance than normal hold-type displays without overdrive. In addition, with the introduction of DID, digital gamma correction [6] needs to be re-examined for its effectiveness, since the LC response is now impulsive, and the color performance may be different. Overdrive, DID, and DGC hardware were developed, and their optical performances that are core to a high quality TFT-LCD, are compared.…”
Section: Introductionmentioning
confidence: 99%